2022
DOI: 10.1038/s41598-022-20594-w
|View full text |Cite
|
Sign up to set email alerts
|

Fate identification and management strategies of non-recyclable plastic waste through the integration of material flow analysis and leakage hotspot modeling

Abstract: Low priority on waste management has impacted the complex environmental issue of plastic waste pollution, as evident by results of this study where it was found that 24.3% of waste generation in Jakarta and Bandung is emitted into the waterway due to the high intensity of human activity in the urban area. In this study, we investigated the viable integration between material flow analysis and leakage hotspot modeling to improve management strategies for plastic pollution in water systems and open environments.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…This finding is somehow in accordance with that in ref. 13 who found urban areas in Jakarta and Bandung emitted the highest waste into the water way. (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is somehow in accordance with that in ref. 13 who found urban areas in Jakarta and Bandung emitted the highest waste into the water way. (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A more recent study on the Carpathian region identifies that watercourses below 750 m.a.s.l are significantly affected by mismanaged plastic waste and most of the hotspots are located in Romania, Hungary, and the Ukraine 12 . Another study revealed that 24.3% of waste generation in Jakarta and Bandung (Indonesia) ends up in waterways with highest plastic accumulation in the mainstream of the Ciliwung and Cikapundung rivers 13 . Moreover, a recent assessment demonstrates that United States generated the largest amount of plastic waste in 2016, of which between 0.14 and 0.41 Mt was illegally dumped and 0.15–0.99 Mt was exported as recycling material that ended up being inappropriate managed 14 .…”
Section: Introductionmentioning
confidence: 99%
“…We chose 1 km of MSW fate leakage into aquatic environments based on the three highest levels of fate leakage potential factors in ref 32 , which refer to point sources in close proximity to < 1km to water systems. This approach has been applied to identify the fate, leakage hotspots and management strategies of non-recyclable plastic waste in Indonesia 5 . A distance of 1km has been used to estimate the vulnerability of mountain rivers to waste dumping in Romania 33…”
Section: Assessment Of Potential Leakage Of Msw Into Rivers Lakes And...mentioning
confidence: 99%
“…Regional studies include an analysis of rural plastic emissions into the Izvoru Muntelui lake (Eastern Carpathians) which suggests that rural municipalities might be responsible for 85.51% of plastic bottles collected between 2005 and 2010 and it concludes that plastic pollution is mainly local 12 . Another study revealed that 24.3% of waste generation in Jakarta and Bandung (Indonesia) ends up in waterways with highest plastic accumulation in the mainstream of the Ciliwung and Cikapundung rivers 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the evaluation results, the effectiveness of recycling plastic waste collected in Banyuwangi and Muncar Districts is significantly lower than the effectiveness of its collection. The low ability of waste facilities to recycle can be caused by contamination of other household waste with plastic waste that is affecting the quality of plastic waste or the absence of a recycling method for plastic waste that is difficult to recycle such as diaper waste, multilayer plastic packaging, used plastic toys, and other plastic waste [8].…”
Section: Evaluation Of Plastic Waste Managementmentioning
confidence: 99%